Analisis Stres Kerja Pada Pekerja Bagian Produksi Springbed - Saputri, Erianda; Dewi, Lisneni; Hariani, Yulia (Institut Citra Internasional, 2024)
The problem of work stress in an organization is an indication that needs to be observed since demands for efficiency in work begin to emerge. Leaders need to manage work stress effectively so that its negative impact on the company can be minimized. Work stress can cause individuals or employees to experience ongoing anxiety, increased emotional tension, disturbances in thought processes, and significant physical impacts. The aim of the research is to analyze work stress in production workersSpring bed at Company X. The type of research used is a quantitative approachcross sectional. The sample in this study consisted of 62 workers. Data analysis using testschi square. The results showed that there was a significant relationship between age (p-value 0.017), gender (p-value 0.017) and work time (p-value 0.04) with work stress. There is no relationship between work fatigue (p-value 0.66) with work stress. This is caused by two factors, namely work environment and organizational factors. Workers are expected to use rest time to stretch their muscles, ensure adequate nutritional and mineral water intake, and comply with guidelines for using personal protective equipment to maintain occupational safety and health.